Study of migration plans for IP - Visut Angkasuwan (2008)
We first review overall concepts of each transition mechanism and transition strategy provided in the newly proposed transition scheme—the DSTM (Dual Stack Transition Mechanism). The DSTM basically offers the transition plan of IPv4-to-IPv6 based on the domain-by-domain transitional approach. Besides, the DSTM defines the use of the IPv4-over-IPv6 tunneling technique to allow the underlying IPv6-only network to carry IPv4 packets when IPv6 node has to communicate with other nodes by using IPv4 packets. Moreover, the mechanism of assigning IPv4 addresses to IPv6 nodes and mechanism to resolve TEP-address for tunneling process are described in the DSTM as well. Next, we illustrate the process how two nodes can interoperate with each other in various cases by the aid of mechanisms and strategies of the DSTM. Besides, we discuss the scalability of the DSTM scheme when it is deployed in the situation where the environment of the Internet has been changed. We envision that the network topology of the Internet will be changed when the transition process is kicked off and has continued for a period of time. Therefore the limitations of the DSTM scheme can be anticipated for each time frame of the transition process. Consequently, we introduced some solutions to resolve problems and to relax the limitations of DSTM. The solutions consist of the new tunnel configurations and the new TEP address resolutions that are designed to suit to the situation of each time frame of the transition process. Finally we also depict several interoperation processes by using the new solutions introduced in this dissertation.